IMPLEMENTASI DATA MINING MENGGUNAKAN MULTI REGRESI UNTUK MEMPREDIKSI RERATA KEDATANGAN MASYARAKAT - Dwi Marisa Efendi; Ferly Ardhy; Riski Oskar Pratama; Sigit Mintoro (Jurnal informasi dan komputer, 2020)
This research uses multiple linear regression methods. research is useful to predicate the average number of people's arrival. this research uses Microsoft Excel 2010 and Rapid miner applications. The variables used are independent variables, free: stock blangko, operator, and working time. predicted to use sample x1 = 795,x2= 3 people, x3= 7 hours , and y= 296 people. Prediction result is -92.2484452, error value data 0.548 and 0.548 for public arrivals.